Translating catechisms, translating cultures: the expansion of Catholicism in the early modern world - Flüchter, Antje; Wirbser, Rouven (Studies in Christian mission, 2017)
Preliminary Material -- Translating Catechisms, Translating Cultures: An Introduction /Antje Flüchter -- Reflection on Language in Christian Mission: The Significance of Communication in the Linguistic Concepts of José de Acosta sj and Antonio Ruiz de Montoya sj /Renate Dürr -- Wholesome Milk and Strong Meat: Peter Canisius’s Catechisms and the Conversion of Protestant Britain /Alexandra Walsham -- Inventing New Words: Father Jean de Brébeuf’s Wendat Catechism of 1632 /John Steckley -- The Writing Catechism and Translation Strategies of Three Jesuits in South India: Henrique Henriques, Roberto de Nobili and Joseph Beschi /Anand Amaladass -- António Fernandes and His Book on the Virgin Mary: A Contribution to the Jesuit-Ethiopian Debate over Asceticism and Matrimony /Leonardo Cohen -- Roberto Nobili’s Vivāha dharma: A Case of Cultural Translation /Giulia Nardini -- A Law Too Strict? The Cultural Translation of Catholic Marriage in the Jesuit Mission to Japan /Rouven Wirbser -- Christian Catechisms and Practice in Japan in the Era of the Jesuit Mission: An Intercultural Approach /Takao Abé -- From Catechisms to Prayer Books in the Early Jesuit China Mission: Tracing the Images the Chinese “should and should not venerate” (16th–17th Centuries) /Ana Carolina Hosne -- Preaching with Pictures, Transforming Memories: Catechisms and Images as Contact Zones in Sixteenth Century New Spain /John Ødemark -- Index.